ACTIVITATEA DE VOLUNTARIAT ÎN ÎNTREBĂRI ŞI RĂSPUNSURI - COŞERIU, director adjunct BM „B.P. Hasdeu”, Tatiana; editor (BIBLIOPOLIS, 2020)
There are many ways to change something. In order to highlight these eff orts and to encourage the citizens the European Commission inaugurated the European Year of Volunteering 2011. Viviane Reding, the Vice President, European commissioner for justice, fundamental rights and citizenship, with Jean- Marc Delizée, the State Secretary for Social Aff airs of Belgium and Marian Harkin, MEP, launched the slogan of “Give you a volunteer! Change something!” The public libraries are at the initial stage of implementation of voluntary work. The European Year of Volunteering is an opportunity to promote this concept and to highlight the social responsibility of a documentary institution. The Strategic Plan for the 2008-2017 of the Municipal Library, B.P. Hasdeu supports the voluntary work as an activity of the durable development. The article, signed by Tatiana Coseri, deputy- director of the Municipal Library, is about the implementation of the quality practices of volunteering.